Living in Nazi Germany (Exploring cultural history, 2004)
People's experience of life in Nazi Germany depended on their perspective. In many ways, those close to Nazi power centers, ordinary Germans and people who were targets of Nazi brutality lived in separate worlds. This anthology covers a variety of viewpoints -- from the commandant of an extermination camp to a pair of Jewish musicians who fled Germany to a girl whose father was killed while fighting in the German army.